Implantable cardioverter-defibrillator in a patient with dextrocardia situs inversus - Mehrdad Saravi; Rozita Jalalian; Mohammadtaghi Hedayati (Babol University of Medical Sciences, 2016)
Background: Dextrocardia is a congenital anomaly, which may have coexistent coronary artery disease (CAD), arrhythmias and conventional indications for device therapy. However, the implantation of transvenous leads can be technically challenging and the approach needs to be tailored to the patient's individual anatomy. Case presentation: A 54-year-old male with dextrocardia situs inversus and ischemic left ventricular dysfunction developed ventricular tachycardia and fibrillation. Therefore, left- sided approach, dual chamber implantable cardioverter-defibrillator (ICD) was applied using a conventional method and standard equipment after complete evaluation of cardiac anatomy and vascular assessment. Conclusion: Electrical device implantation in patients with dextrocardia is possible after obtaining complete information about anatomy and/or coexisting congenital abnormalities, which helps in obtaining appropriate implantation approach.